715 Implementation of Enhanced Recovery After Surgery (ERAS) in Total Laryngectomies. (19th August 2022) - Lim, KH; Dorris, C; Thomson, A; Ardis, M; Devlin, B; Gray, G
Abstract: Aim: The Enhanced Recovery After Surgery (ERAS) protocol for total laryngectomies was first implemented in our tertiary head and neck centre from November 2019. It includes pre-operative carbohydrate loading and an early swallow test which facilitates recommencement of oral intake to improve outcomes. Protocol adherence rate and patient outcomes were measured to determine the effectiveness and benefits of ERAS in laryngectomy patients. Method: 22 total laryngectomy patients from November 2019 to September 2021 were enrolled onto the ERAS protocol, 18 primary and 3 salvage cases. An analysis of the respective patient cohorts was performed to determine adherence to the ERAS protocol and outcomes such as complications and length of inpatient stay were measured. Results: 19 patients (86%) received pre-operative carbohydrate loading successfully, while 3 patients were contraindicated due to background of diabetes. Early swallow test was performed in 59% of patients. Potential reasons for delay were stoma dehiscence or clinical suspicion of neo-pharyngeal leak. 59% of primary cases were deemed medically fit for discharge within the target timeframe of 12–14 days whereas no target was set for salvage cases due to expected poor healing. Main complication in primary cases was neo-pharyngeal leak followed by stoma dehiscence with 28% and 11% respectively. Conclusion: Limitations of our study include small sample size due to the COVID-19 pandemic. Despite its infancy, the ERAS protocol has achieved good outcomes in early recommencement of oral intake post-laryngectomy and encouraging early safe discharge from hospital. Future plans include establishment of Prehab Clinic and application of ERAS to neck dissection patients.